ANALISIS STRUKTUR ANGGARAN BIDANG PEMBERDAYAAN MASYARAKAT APBKAL SITIMULYO TAHUN 2026 - Amira Putri Ramadhani; Nur Laila Sari; Illiyin Aulia Fadhilah; Viena Kurniawan (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
This study aims to analyze the proportion and distribution of the Community Empowerment budget in the APBKal of Kalurahan Sitimulyo for the 2026 fiscal year and evaluate its alignment with inclusive development principles. The study employs a descriptive quantitative approach using APBKal documents, supported by limited interviews and observations. The results show that the allocation for community empowerment accounts for only 4.63% of total village expenditure, with an uneven distribution dominated by agriculture, livestock, and industrial sectors. Meanwhile, areas related to inclusivity, such as women’s empowerment, child protection, and MSMEs, receive relatively small portions. This indicates that budgeting remains oriented toward production-based economic sectors, and the principles of equity and inclusiveness have not been proportionally reflected. Although it refers to SDGs Desa and gender mainstreaming principles, their implementation still requires strengthening.